Integrasi nilai-nilai islam dalam manajemen strategi dan pemasaran jasa: Dampaknya terhadap loyalitas nasabah bank BRI Syariah - nabila, fiqrotun (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of strategic management in enhancing customer loyalty at BRI Syariah Bank through the application of Islamic-based service marketing. In the midst of increasing competition in the banking industry, Islamic financial institutions are required not only to pursue profitability but also to embed Islamic values in every operational aspect. This research adopts a descriptive qualitative approach using a case study method at BRI Syariah, with data collected through observation, in-depth interviews, and documentation analysis. The results indicate that the implementation of a well-structured and Sharia-oriented management strategy covering planning, execution, and supervision has successfully strengthened customer trust and loyalty. Service strategies emphasizing justice, transparency, and professionalism have significantly contributed to improving customer relationships. Moreover, Islamic service marketing, which highlights spiritual and emotional engagement, plays a vital role in shaping BRI Syariah’s positive image within the competitive banking sector. Hence, the integration of modern management strategies with Islamic ethical principles serves as the foundation for sustaining customer loyalty and enhancing the competitive position of Islamic banks in Indonesia.